Silicon carbide microstructure and compressive resistance change test platform and construction method thereof

By designing the silicon carbide microstructure and its piezores resistance change test platform, the lack of effective methods for the research on the piezores resistance change of the silicon carbide epitaxial layer in the existing technology is solved, and experimental verification methods are provided, which meets the different doping and infiltrating conditions. The resistance change test requirements provide a theoretical basis for the design of silicon carbide sensor chips.

CN119263203APending Publication Date: 2025-01-07XI AN JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411377951.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing technology lacks effective experimental verification methods to study the resistance change characteristics of the silicon carbide epitaxial layer after being compressed, resulting in the lack of a reliable theoretical basis for the design of related sensor chips.

Method used

A silicon carbide microstructure and its piezoresistance resistance change test platform were designed to study the resistance change characteristics of the silicon carbide epitaxial layer under different doping types and concentrations through experimental qualitative and quantitative analysis, including high doping wetting and light Through the steps of engraving process and thermal annealing, a debuggable test platform is built.

Benefits of technology

It provides effective experimental research methods, simplifies platform construction, reduces costs, and realizes the theoretical basis for the design and optimization of silicon carbide sensor chip structure, providing technical reference for semiconductor materials research.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005069156500000011
    Figure HDA0005069156500000011
  • Figure HDA0005069156500000021
    Figure HDA0005069156500000021
  • Figure HDA0005069156500000031
    Figure HDA0005069156500000031
Patent Text Reader

Abstract

The invention discloses a silicon carbide microstructure and a compressive resistance change test platform and a building method thereof, the microstructure comprises a silicon carbide microstructure with a high-doping-concentration epitaxial layer, the high-doping-concentration silicon carbide microstructure is a multi-layer silicon carbide epitaxial wafer obtained through N-type or P-type epitaxial doping, a surface-layer micro sensitive resistor is prepared through a micro-nano process, and the surface-layer micro sensitive resistor is provided with a high-doping-concentration epitaxial layer. Every two miniature sensitive resistors are the same in size, and the shape centers of the miniature sensitive resistors are located at the same axial position on the silicon carbide microstructure and are vertically distributed in the transverse direction. Aiming at the highly-doped silicon carbide microstructure, a compressive resistance change test platform is built, and a laboratory-level and low-cost compressive resistance change test of the silicon carbide microstructure is realized through pasting fixation and wire connection; according to the invention, the resistance change characteristics of the silicon carbide epitaxial layer after being pressed under different doping types and concentrations can be qualitatively and quantitatively researched from the perspective of experiments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of semiconductor micro-nano processing and testing, and in particular relates to a silicon carbide microstructure and a pressure resistance change test platform and a construction method thereof. Background Art

[0002] Silicon carbide, as a typical representative of the third generation of wide bandgap semiconductors, has material advantages such as high thermal conductivity, corrosion resistance, wide bandgap, and high carrier mobility, and is widely used in fields such as microelectronics and micro-nano sensors. In the field of power devices, silicon carbide is used as the main substrate material for the preparation of metal-oxide semiconductor field effect transistors (MOSFETs), which have higher tolerance temperatures and operating voltages, and significantly reduced on-resistance and switching losses. In view of its excellent mechanical, electrical, and chemical properties, in recent years, the preparation of micro-nano special sensors with good working characteristics using silicon carbide as a substrate has become an important breakthrough direction for solving the measurement of many physical quantities in high-temperature and harsh environments.

[0003] At present, various types of silicon carbide pressure, strain and acceleration sensor chips mainly rely on the sensitive characteristics of resistance change after pressure of highly doped silicon carbide epitaxial layer to realize physical quantity perception. However, the pressure sensitive characteristics of silicon carbide epitaxial layer with different doping concentrations are mainly based on multi-physical field coupling simulation modeling. For example, in the paper [Toriyama T, Sugiyama S. Analysis of piezoresistance in n-type 6H SiC for high-temperature mechanical sensors [C] / / TRANSDUCERS'03.12th International Conference on Solid-State Sensors, Actuators and Microsystems. Digest of Technical Papers (Cat. No.03TH8664). IEEE, 2003, 1:758-761.], complex theoretical calculations and deductions were made for the resistance change of N-type 6H silicon carbide after pressure, but no relevant experimental verification methods were found, which made the theoretical deduction less reliable and complete. In general, the current research on the resistance change of silicon carbide after being compressed lacks effective research methods and no intuitive experimental test results, resulting in a lack of reliable theoretical basis and design basis for related sensor chips during the design stage. Summary of the invention

[0004] In order to overcome the above-mentioned shortcomings of the prior art, the present invention proposes a silicon carbide microstructure and a pressure resistance change test platform and construction method thereof, which can qualitatively and quantitatively study the resistance change characteristics of silicon carbide epitaxial layers under different doping types and concentrations after being compressed from an experimental perspective, and provide a theoretical basis for the structural design and optimization of related silicon carbide sensor chips. It has the characteristics of adjustable test object parameters (number of layers, thickness) and a simple and easy to build test platform.

[0005] To achieve the above object, the technical solution of the present invention is:

[0006] A silicon carbide microstructure with a highly doped epitaxial layer with a doping concentration of 1e18 cm -3 —1e20cm -3 .

[0007] The silicon carbide microstructure with a high doping concentration epitaxial layer comprises an N-type single crystal silicon carbide substrate 101, on which is a P-type doped epitaxial layer 102 with a high doping concentration;

[0008] Alternatively, the structure of the multi-layer silicon carbide epitaxial wafer 100 is formed by stacking a P-type doped epitaxial layer 102 and an N-type doped epitaxial layer 103 with a high doping concentration.

[0009] The high doping concentration P-type doping refers to the epitaxial growth of gaseous substances containing aluminum Al elements on the single crystal silicon carbide substrate 101; the high doping concentration N-type doping refers to the epitaxial growth of gaseous substances containing nitrogen elements on the P-type doped epitaxial layer 102 of the single crystal silicon carbide substrate 101.

[0010] The silicon carbide microstructure with a high doping concentration epitaxial layer has an overall structural size of 25-45 mm in length, 4-6 mm in width, and 300-350 μm in thickness; wherein the high doping concentration P-type doped epitaxial layer 102 is 2-5 μm thick, and the high doping concentration N-type doped epitaxial layer 103 is 2-5 μm thick.

[0011] The preparation method of the silicon carbide microstructure with a high-doping concentration epitaxial layer comprises the following steps:

[0012] Step 1: epitaxially grow a single crystal silicon carbide substrate 101 by introducing a gaseous substance containing aluminum Al element to form a 2-5 μm thick and doping concentration of 1e18 cm -3 —1e20cm -3 The P-type doped epitaxial layer 102 is NP-type; or the gaseous substance containing nitrogen is continued to pass through to form a doping concentration of 1e18cm -3 —1e20cm -3 The N-type doped epitaxial layer 103 is finally combined to form a multi-layer silicon carbide epitaxial wafer 100, which is an NPN type;

[0013] Step 2: Using an acetone solution to soak and clean the multilayer silicon carbide epitaxial wafer 100 obtained in step 1 to remove organic impurities on the surface; then using anhydrous ethanol to remove the acetone residue, and then repeatedly rinsing with deionized water and drying;

[0014] Step 3, coating the surface of the multi-layer silicon carbide epitaxial wafer 100 cleaned in step 2 with a photoresist having a thickness of 1 μm to 6 μm, and patterning the surface through a primary photolithography process to obtain a once patterned multi-layer silicon carbide epitaxial wafer 100;

[0015] Step 4, dry-etching the once patterned multi-layer silicon carbide epitaxial wafer 100 obtained in step 3 to form a surface micro-sensitive resistor 104, and then immersing it in an acetone solution to remove the surface photoresist and clean it;

[0016] Step 5, depositing an insulating layer 105 with a thickness of 50 nm to 500 nm on the surface of the multilayer silicon carbide epitaxial wafer 100 obtained in step 4;

[0017] Step 6, coating the surface of the multilayer silicon carbide epitaxial wafer 100 obtained in step 5 with photoresist for the second time, and patterning it through a secondary photolithography process to form a contact lead window pattern, and then immersing it in a BOE solution to remove silicon dioxide from the uncovered area to form a contact lead window 106;

[0018] Step 7, coating the surface of the multilayer silicon carbide epitaxial wafer 100 obtained in step 6 with a photoresist having a thickness of 1 μm to 6 μm for the third time, patterning the contact lead pattern through three photolithography processes, depositing a metal layer on the surface thereof, and forming a conductive contact lead 107 through a lift-off process;

[0019] Step 8: subject the multilayer silicon carbide epitaxial wafer 100 obtained in step 7 to high temperature thermal annealing at a temperature of 600° C. to 1200° C. for a time of 1 min to 30 min, and then slice and cut it to obtain a sample of the silicon carbide microstructure 1 to be tested.

[0020] The single crystal silicon carbide substrate 101 in step 1 includes a single crystal silicon carbide wafer of any size including 4H-SiC and 6H-SiC.

[0021] The number of the surface micro-sensitive resistors 104 obtained in step 4 is an even number, and there are 2 surface micro-sensitive resistors of each size, and the shape centers of the two surface micro-sensitive resistors 104 are at the same axial position on the surface of the silicon carbide microstructure 1, but are distributed perpendicular to each other in the lateral direction.

[0022] In step 5, the insulating layer 105 is a silicon nitride layer, a silicon oxide layer, or a composite structure of a silicon nitride layer and a silicon oxide layer.

[0023] The BOE solution in step 6 is formed by mixing a hydrofluoric acid solution with a mass concentration of 49% and an ammonium fluoride solution with a mass concentration of 40% in a volume ratio of 1:6.

[0024] The metal layer in step 7 is a single-layer or multi-layer conductive metal layer composed of any metal or alloy combination, and its thickness is 100-500nm.

[0025] The contact lead 107 in step 7 is connected to the lead pad 108 for realizing electrical connection with the outside world.

[0026] The cutting methods used in step 8 include mechanical cutting with a diamond wheel and laser cutting.

[0027] The photoresist is AZ4620 positive photoresist.

[0028] A test platform for the resistance change of a silicon carbide microstructure under pressure, comprising a clamping platform 202 with an adjustable spacing, a sample fixing substrate 201 is provided at the supporting end of the clamping platform 202 with an adjustable spacing, a sample of a silicon carbide microstructure 1 is pasted on the sample fixing substrate 201, a lead pad 108 on the silicon carbide microstructure 1 is connected with a wire 205, the other end of the wire 205 is connected to an ohmmeter 206, a hook 203 is provided at the edge of the silicon carbide microstructure 1, and standard weights 204 of different weights are hung on the hook 203 in sequence.

[0029] The method for constructing the pressure resistance change test platform comprises the following steps:

[0030] Step 1, pasting the silicon carbide microstructure 1 with a highly doped epitaxial layer on the sample fixing substrate 201, and then holding the sample fixing substrate 201 on a clamping platform 202 with an adjustable spacing;

[0031] Step 2, welding one end of the wire 205 to the lead pad 108 on the silicon carbide microstructure 1, and connecting the other end of the wire to the ohmmeter 206;

[0032] Step 3, sticking and fixing the hook 203 on the edge of one end of the silicon carbide microstructure 1 with a highly doped epitaxial layer, and using it to hang the standard weight 204 after solidification;

[0033] Step 4: hang standard weights 204 of different weights on the hook 203 in sequence, and read the resistance value change on the silicon carbide microstructure 1 with a highly doped epitaxial layer from the ohmmeter 205 .

[0034] The adhesives involved in the construction steps are all epoxy resin adhesives or other adhesives with high bonding strength.

[0035] The sample fixing substrate 201 is a PCB board with metal pad connection points, or an alumina ceramic substrate or an aluminum nitride ceramic substrate with metal pad connection points.

[0036] Compared with the prior art, the present invention has the following beneficial technical effects:

[0037] (1) A silicon carbide microstructure of the present invention can meet the test requirements of resistance change of epitaxial silicon carbide with different doping after being compressed by adjusting the doping parameters of the microstructure. The microstructure has the advantages of small size and simple preparation process.

[0038] (2) The present invention provides an effective experimental research method for studying the resistance characteristics of silicon carbide epitaxial layers with different doping concentrations after being subjected to pressure. The platform construction method is simple in steps, low in cost, and easy to implement; it breaks away from the limitation that the resistance change characteristics can only be studied through simulation methods.

[0039] In summary, the silicon carbide microstructure and its pressure resistance change test platform and construction method provided by the present invention have universal adaptability and provide a technical reference for the research of other semiconductor materials with similar pressure resistance change characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 It is a three-dimensional schematic diagram of the pressure resistance change test platform 2 of the present invention.

[0041] Figure 2 Schematic diagram of silicon carbide microstructure of the present invention, wherein: Figure 2 (a) is an isometric view; (b) is a top view; and (c) is a left view.

[0042] Figure 3 The figure is a flow chart of the process steps for preparing the silicon carbide microstructure of the present invention.

[0043] In the figure: 1-silicon carbide microstructure, 2-pressure resistance change test platform, 100-multilayer silicon carbide epitaxial wafer, 101-single crystal silicon carbide substrate, 102-P-type doped epitaxial layer, 103-N-type doped epitaxial layer, 104-surface micro-sensitive resistor, 105-insulating layer, 106-contact lead window, 107-contact lead, 108-lead pad, 201-sample fixing substrate, 2011-substrate metal pad connection point, 202-clamping platform with adjustable spacing, 203-hook, 204-standard weight, 205-wire, 206-ohmmeter. DETAILED DESCRIPTION

[0044] In order to make the purpose and technical solution of the present invention clearer and easier to understand, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0045] See also Figure 2 , a silicon carbide microstructure, which is marked as a silicon carbide microstructure 1 in the figure, has a high doping concentration epitaxial layer, and is an NPN type multi-layer substrate structure epitaxially formed on a four-inch N-type single crystal 4H-SiC substrate; specifically: having a high doping concentration epitaxial layer, is a multi-layer silicon carbide epitaxial wafer 100 structure composed of a high doping concentration P-type doped epitaxial layer 102 and an N-type doped epitaxial layer 103, which are layered and combined.

[0046] The high doping concentration P-type doping refers to the epitaxial growth of gaseous substances containing aluminum Al elements on the single crystal silicon carbide substrate 101; the high doping concentration N-type doping refers to the epitaxial growth of gaseous substances containing nitrogen elements on the P-type doped epitaxial layer 102 of the single crystal silicon carbide substrate 101.

[0047] The silicon carbide microstructure with a high doping concentration epitaxial layer has an overall structural size of: 25-45 mm in length, 4-6 mm in width, and 300-350 μm in thickness; wherein the single crystal silicon carbide substrate 101 is 298-340 μm thick, the high doping concentration P-type doped epitaxial layer 102 is 2-5 μm thick, and the high doping concentration N-type doped epitaxial layer 103 is 2-5 μm thick.

[0048] See also Figure 2 The silicon carbide microstructure 1 with a high doping concentration epitaxial layer has an overall structural size of 25 to 45 mm in length, 4 to 6 mm in width, and 300 to 350 μm in thickness.

[0049] See also Figure 2 , Figure 3 The silicon carbide microstructure having epitaxial layers with different doping concentrations, and the preparation method thereof comprises the following process:

[0050] Step 1: Epitaxial growth is performed on the 4H single crystal silicon carbide substrate 101, and a gaseous substance containing Al is introduced to form a layer with a thickness of 5 μm and a doping concentration of 1e18 cm -3 The P-type doped epitaxial layer 102 is then introduced with a gaseous substance containing nitrogen to form a 2 μm thick layer with a concentration of 1e19 cm -3 The N-type doped epitaxial layer 103 is finally obtained to obtain an NPN-type (the substrate itself is N-type) multilayer silicon carbide epitaxial wafer 100;

[0051] Step 2, soaking and cleaning the multilayer silicon carbide epitaxial wafer 100 obtained in step 1, immersing it in an acetone solution to remove organic impurities on the surface, then using anhydrous ethanol to remove residual acetone, and then repeatedly rinsing it with deionized water and drying it;

[0052] Step 3, coating the surface of the multi-layer silicon carbide epitaxial wafer 100 cleaned in step 2 with AZ4620 positive photoresist having a thickness of 4 μm, and patterning the surface through a photolithography process of spin coating photoresist-pre-bake-exposure-development-post-bake, etc., to obtain a once patterned multi-layer silicon carbide epitaxial wafer 100;

[0053] Step 4, dry-etching the once patterned multilayer silicon carbide epitaxial wafer 100 obtained in step 3 to form a surface micro-sensitive resistor 104, immersing the obtained multilayer silicon carbide epitaxial wafer 100 in an acetone solution to remove the surface photoresist and clean it;

[0054] Step 5: On the surface of the multilayer silicon carbide epitaxial wafer 100 obtained in step 4, a silicon dioxide insulating layer 105 with a thickness of 300 nm is deposited by plasma chemical vapor deposition;

[0055] Step 6, coating the surface of the multilayer silicon carbide epitaxial wafer 100 obtained in step 5 with a 4 μm thick AZ4620 positive photoresist for the second time, and patterning it through a secondary photolithography process to form a contact lead window pattern, and then immersing it in a BOE solution formed by mixing a hydrofluoric acid solution with a mass concentration of 49% and an ammonium fluoride solution with a mass concentration of 40% in a volume ratio of 1:6, removing silicon dioxide from the uncovered portion, and forming a contact lead window 106;

[0056] Step 7, coating the surface of the multilayer silicon carbide epitaxial wafer 100 obtained in step 6 with AZ4620 positive photoresist with a thickness of 4 μm for the third time, and patterning it through three photolithography processes to form a contact lead pattern, then depositing Ni with a thickness of 100 nm and W with a thickness of 200 nm on the surface to form a Ni / W metal layer, and forming a conductive contact lead 107 through a lift-off process;

[0057] Step 8, subjecting the multilayer silicon carbide epitaxial wafer 100 obtained in step 7 to high temperature thermal annealing, the annealing condition being a temperature of 1000° C. for 2 min, and using laser scribing to cut it into a plurality of silicon carbide microstructure 1 samples to be tested with dimensions of 45 mm in length, 5 mm in width, and 350 μm in thickness;

[0058] The silicon carbide microstructure 1 with a highly doped epitaxial layer described in the above embodiment of the present invention, the single crystal silicon carbide substrate in the preparation process step 1 may also be a single crystal silicon carbide wafer of any size including 4H-SiC and 6H-SiC;

[0059] The silicon carbide microstructure 1 with a highly doped epitaxial layer described in the above scheme of the present invention has four surface micro-sensitive resistors 104 obtained in the preparation process step 4, two of which have the same size and whose shape centers are located at the same axial position of the silicon carbide microstructure 1, but are arranged perpendicular to each other in the lateral direction.

[0060] The silicon carbide microstructure 1 with a highly doped epitaxial layer described in the above embodiment of the present invention, wherein the contact wire 107 in the preparation process step 9 comprises a wire pad 108 for realizing electrical connection with the outside world;

[0061] The silicon carbide microstructure 1 with a highly doped epitaxial layer described in the above embodiment of the present invention has a cutting method used in step 10 of the preparation process including mechanical cutting with a diamond wheel, laser cutting and the like.

[0062] See also Figure 1 A pressure resistance change test platform 2 for a silicon carbide microstructure comprises a clamping platform 202 with an adjustable spacing, a sample fixing substrate 201 is provided at the supporting end of the clamping platform 202 with an adjustable spacing, a sample of a silicon carbide microstructure 1 is pasted on the sample fixing substrate 201, a wire 205 is connected to the lead pad 108 on the silicon carbide microstructure 1 (welded by an electric soldering iron, the welding point is the substrate metal pad connection point 2011), the other end of the wire 205 is connected to an ohmmeter 206, a hook 203 is provided at the edge of the silicon carbide microstructure 1, and standard weights 204 of different weights are hung on the hook 203 in sequence.

[0063] The steps of constructing the pressure resistance change test platform 2 include:

[0064] Step 1, pasting the silicon carbide microstructure 1 with a highly doped epitaxial layer on the sample fixing substrate 201; and then holding the sample fixing substrate 201 on a clamping platform 202 with an adjustable spacing;

[0065] Step 2: A plurality of lead pad connection points 2011 are prepared on the silicon carbide microstructure 1 with a highly doped epitaxial layer. One end of the wire 205 is welded to the lead pad 108 on the silicon carbide microstructure 1 using an electric soldering iron, and the other end of the wire is connected to an ohmmeter 206;

[0066] Step 3: Use epoxy resin adhesive to stick and fix the hook 203 to the edge of one end of the silicon carbide microstructure 1 with a highly doped epitaxial layer, and after curing at 60° C. for 4 hours, use it to hang the standard weight 204;

[0067] Step 4. Hang standard weights on the hook in sequence, from 0g, 5g, 15g, 20g, 25g, 30g, 35g, 40g, 45g, 50g, 55g, 60g, 65g, 70g, and read the changes in resistance values ​​from the ohmmeter in sequence.

[0068] The sample fixing substrate 201 in the pressure resistance change test platform 2 described in the above scheme of the present invention is a PCB board with metal pad connection points 2011, or an alumina ceramic substrate or an aluminum nitride ceramic substrate with metal pad connection points.

[0069] When preparing silicon carbide microstructures with high-doping concentration epitaxial layers, the doping concentration, number of layers and thickness are changed. The above-mentioned platform and construction method can be used to study the resistance change characteristics of silicon carbide epitaxial layers under different doping types and concentrations after being compressed, providing a theoretical basis for the structural design and optimization of related silicon carbide sensor chips.

[0070] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A silicon carbide microstructure, characterized in that: High doping concentration epitaxial layer, doping concentration 1e18cm -3 —1e20cm -3 ; The silicon carbide microstructure with a high-doping concentration epitaxial layer comprises an N-type single-crystal silicon carbide substrate (101), and a P-type doped epitaxial layer (102) with a high doping concentration is formed on the single-crystal silicon carbide substrate (101); Alternatively, the invention provides a multi-layer silicon carbide epitaxial wafer (100) structure formed by combining a P-type doped epitaxial layer (102) and an N-type doped epitaxial layer (103) with a high doping concentration.

2. A silicon carbide microstructure according to claim 1, characterized in that: The high-doping concentration P-type doping refers to epitaxial growth of a gaseous substance containing aluminum (Al) elements on a single-crystal silicon carbide substrate (101); the high-doping concentration N-type doping refers to epitaxial growth of a gaseous substance containing nitrogen elements on a P-type doped epitaxial layer (102) of the single-crystal silicon carbide substrate (101); The silicon carbide microstructure with a high doping concentration epitaxial layer has an overall structural size of 25-45 mm in length, 4-6 mm in width, and 300-350 μm in thickness; wherein the high doping concentration P-type doped epitaxial layer (102) is 2-5 μm thick, and the high doping concentration N-type doped epitaxial layer (103) is 2-5 μm thick.

3. A method for preparing a silicon carbide microstructure according to claim 1 or 2, characterized in that: The process includes the following: Step 1: epitaxially grow a single crystal silicon carbide substrate (101) by introducing a gaseous substance containing aluminum Al element to form a layer with a thickness of 2-5 μm and a doping concentration of 1e18 cm -3 —1e20cm -3 The P-type doped P-type doped epitaxial layer (102) is NP-type; or the gaseous substance containing nitrogen is continued to pass to form a doping concentration of 1e18cm -3 —1e20cm -3 The N-type doped epitaxial layer (103) is finally combined to form a multi-layer silicon carbide epitaxial wafer (100) of NPN type; Step 2: using an acetone solution to soak and clean the multilayer silicon carbide epitaxial wafer (100) obtained in step 1 to remove organic impurities on the surface; then using anhydrous ethanol to remove acetone residues, and then repeatedly rinsing with deionized water and drying; Step 3, coating the surface of the multi-layer silicon carbide epitaxial wafer (100) cleaned in step 2 with a photoresist having a thickness of 1 μm to 6 μm, and patterning the surface through a primary photolithography process to obtain a single-patterned multi-layer silicon carbide epitaxial wafer (100); Step 4, dry etching the once patterned multilayer silicon carbide epitaxial wafer (100) obtained in step 3 to form a surface micro-sensitive resistor (104), and then immersing it in an acetone solution to remove the surface photoresist and clean it; Step 5, depositing an insulating layer (105) with a thickness of 50 nm to 500 nm on the surface of the multilayer silicon carbide epitaxial wafer (100) obtained in step 4; Step 6, coating the surface of the multilayer silicon carbide epitaxial wafer (100) obtained in step 5 with photoresist for a second time, and patterning it through a secondary photolithography process to form a contact lead window pattern, and then immersing it in a BOE solution to remove silicon dioxide from the uncovered area to form a contact lead window (106); Step 7, coating the surface of the multilayer silicon carbide epitaxial wafer (100) obtained in step 6 with a photoresist having a thickness of 1 μm to 6 μm for the third time, patterning the surface of the multilayer silicon carbide epitaxial wafer (100) by three photolithography processes to form a contact lead pattern, depositing a metal layer on the surface of the surface, and forming a conductive contact lead (107) by a lift-off process; Step 8, subjecting the multilayer silicon carbide epitaxial wafer (100) obtained in step 7 to high temperature thermal annealing at a temperature of 600° C. to 1200° C. for a time of 1 min to 30 min, and slicing and cutting it to obtain a sample of the silicon carbide microstructure (1) to be tested.

4. The method for preparing a silicon carbide microstructure according to claim 3, characterized in that: The single crystal silicon carbide substrate (101) in step 1 includes single crystal silicon carbide wafers of any size including 4H-SiC and 6H-SiC.

5. The method for preparing a silicon carbide microstructure according to claim 3, characterized in that: The number of surface micro-sensitive resistors (104) obtained in step 4 is an even number, and there are two surface micro-sensitive resistors of each size, and the shape centers of the two surface micro-sensitive resistors (104) are at the same axial position on the surface of the silicon carbide microstructure (1), but are distributed perpendicular to each other in the transverse direction.

6. The method for preparing a silicon carbide microstructure according to claim 3, characterized in that: In step 5, the insulating layer (105) is a silicon nitride layer, a silicon oxide layer, or a composite structure of a silicon nitride layer and a silicon oxide layer; The BOE solution in step 6 is formed by mixing a hydrofluoric acid solution with a mass concentration of 49% and an ammonium fluoride solution with a mass concentration of 40% in a volume ratio of 1:6; The metal layer in step 7 is a single-layer or multi-layer conductive metal layer composed of any metal or alloy combination, and its thickness is 100 to 500 nm.

7. The method for preparing a silicon carbide microstructure according to claim 3, characterized in that: The contact lead (107) in step 7 is connected to the lead pad (108) to achieve electrical connection of the wire with the outside world; The cutting method used in step 8 includes mechanical cutting with a diamond wheel and laser cutting; The photoresist is AZ4620 positive photoresist.

8. A pressure resistance change test platform for silicon carbide microstructures according to claim 1, characterized in that: The invention comprises a clamping platform (202) with an adjustable spacing, a sample fixing substrate (201) is arranged at the holding end of the clamping platform 202 with an adjustable spacing, a sample of a silicon carbide microstructure (1) is pasted on the sample fixing substrate (201), a lead pad (108) on the silicon carbide microstructure (1) is connected to a wire (205), the other end of the wire (205) is connected to an ohmmeter (206), a hook (203) is arranged at the edge of the silicon carbide microstructure (1), and standard weights (204) of different weights are sequentially hung on the hook (203).

9. The method for constructing a pressure resistance change test platform according to claim 8, characterized in that the steps include: Step 1, pasting a silicon carbide microstructure (1) having a highly doped epitaxial layer onto a sample fixing substrate (201), and then mounting the sample fixing substrate (201) onto a clamping platform (202) with an adjustable spacing; Step 2, welding one end of the wire (205) to the lead pad (108) on the silicon carbide microstructure (1), and connecting the other end of the wire to an ohmmeter (206); Step 3, sticking and fixing the hook (203) on the edge of one end of the silicon carbide microstructure 1 with a highly doped epitaxial layer, and using it to hang a standard weight (204) after solidification; Step 4: hang standard weights (204) of different weights on the hook 203 in sequence, and read the resistance value change on the silicon carbide microstructure (1) with a highly doped epitaxial layer from the ohmmeter (205).

10. The method for constructing a pressure resistance change test platform according to claim 9, characterized in that: The pasting involved in the building steps is epoxy resin adhesive or other adhesives with high bonding strength; the sample fixing substrate (201) is a PCB board with metal pad connection points, or an alumina ceramic substrate or an aluminum nitride ceramic substrate with metal pad connection points.